The influence of sustainopreneurship knowledge and VR literacy on business sustainability perception among borderland women entrepreneurs - Asriati, Nuraini; Fatmawati, Fatmawati; Indrawati, Urai Suci Yulies Vitri; Wardani, Sandra Fitria; Annafiatuzakiah, Annafiatuzakiah (Edelweiss Applied Science and Technology, 2025)
Women-led micro, small, and medium enterprises (MSMEs) in traditional crafts play a crucial role in preserving cultural heritage and fostering local economic resilience, especially in border regions. However, the sustainability of these enterprises is often challenged by limited technological access and low digital literacy. This study aims to examine the influence of sustainopreneurship knowledge and Virtual Reality (VR) literacy on the perception of business sustainability among female Songket Cual artisans in Sambas District, West Kalimantan. Utilizing a quantitative, associative approach, data were collected from 50 respondents through structured questionnaires and analyzed using multiple linear regression. The results reveal that both independent variables significantly affect the perception of business sustainability (F = 59.523; p < 0.001; R² = 0.616). Sustainopreneurship knowledge and VR literacy synergistically strengthen sustainability perceptions, particularly in terms of innovation, business resilience, and adaptability to technological change. These findings underscore the importance of integrating local cultural values with technological innovation as a strategy for empowering women-led MSMEs in marginalized regions. The study contributes theoretically to the development of a technology-based sustainopreneurship model and offers practical recommendations for designing effective interventions to support the sustainable transformation of culture-based microenterprises.